2014 FIFA World Cup in Brazil: The Effects of Neutrality of Intent and Economic Welfare on Support Intentions. Issue 1 (2nd January 2017) - Rocha, Claudio M.; Gratao, Otavio A.
ABSTRACT: This research aims to describe (1) the impacts of neutrality of intent and economic welfare on expectations of positive legacies, and (2) the impacts of expected positive legacies on support for the 2014 FIFA World Cup. This study drew on social exchange, liberal egalitarianism, and welfare economic theories. Participants ( n = 254) were randomly assigned to 1 out of 4 possible treatments, where neutrality of intent in spending public money and likelihood of economic welfare were manipulated. Then, they completed a questionnaire expressing perceptions of positive legacies and support for the 2014 World Cup. Findings showed significant main effects for neutrality of intent, but non-significant main effects for economic welfare. Neutrality of intent increased positive expectations of economic, tourism, and cultural legacies, which in turn explained significant variance in support for the event.